VOYEURISM AS A PSHYCHOSEXUAL DISORDER: A NEED OF THE HOUR1 - Kumar Das, Atin (International Journal of Psychosocial Rehabilitation, 2024)
Until recently, voyeurism did not have its own offence category, coming under the heading of ‘breach of the peace’ or, if a number of victims were involved, ‘being a public nuisance’. Hence the statistics of this type of offence up till now are difficult to come by. Voyeurism, or scopophilia as it is sometimes called, is of theoretical interest beyond its forensic implications. First, there is a tendency for most people to look at sexually interesting scenes. In some, looking is preferred to actually participating, presumably because real contact is too threatening for one reason or another. This voyeuristic element is sometimes revealed in people’s fantasies, in which they look at other people rather than participate themselves. This can be an important clue to their basic sexual problem.